Visual impairment, severe visual impairment, and blindness in children in Britain (BCVIS2): a national observational study. (March 2021) - Teoh, Lucinda J; Solebo, Ameenat Lola; Rahi, Jugnoo S; ,; Morton, Claire; Allen, Louise; McPhee, Derek; Brennan, Rosie; Pennefather, Philippa; Kattakayan, Charles; Ramm, Laura; Abbott, Joe; et al.
Summary: Background: The WHO VISION 2020 global initiative against blindness, launched in 2000, prioritised childhood visual disability by aiming to end avoidable childhood blindness by 2020. However, progress has been hampered by the global paucity of epidemiological data concerning childhood visual disability. The British Childhood Visual Impairment and Blindness Study 2 (BCVIS2) was done to address this evidence gap. Methods: BCVIS2 was a prospective UK-wide, cross-sectional, observational study to establish an inception cohort of children newly diagnosed with visual impairment. Opthalmologists and paediatricians reported cases from 89 hospitals and community centres across the UK. We included children aged 18 years or younger who were newly diagnosed with any condition causing impaired visual acuity to a level of 0·5 logMAR or worse (worse than 6/18 Snellen) in each eye, or equivalent vision as assessed by standard qualitative measures, between Oct 1, 2015, and Nov 1, 2016. Eligible children were notified simultaneously but independently by their managing ophthalmologists and paediatricians via the two national active surveillance schemes, the British Ophthalmological Surveillance Unit and the British Paediatric Surveillance Unit. Standardised detailed demographic, socioeconomic, and clinical data about detection, management, and treatment were collected at diagnosis and 1 year later. We calculated incidence estimates and relative rates by key sociodemographic factors. We did descriptive analyses of underlying ophthalmic disorders and non-ophthalmic comorbidities. Findings: 61 (7%) of 845 eligible children initially notified were ineligible at follow-up because of improved vision after treatment. Thus, the study sample comprised 784 children with permanent newly-diagnosed all-cause visual impairment, severe visual impairment, or blindness. 559 (72%) of 778 children had clinically significant non-ophthalmic impairments or conditions. 28 (4%) of 784 children died within a year after diagnosis of visual disability (all had underlying systemic disorders). Incidence of visual disability in the first year of life was 5·19 per 10 000 children (95% CI 4·71–5·72), almost ten times higher than among 1-to-4-year-olds and between 20 times and 100 times higher than in the older age groups. The overall cumulative incidence (or lifetime risk) of visual impairment, severe visual impairment, or blindness was 10·03 per 10 000 children (9·35–10·76). Incidence rates were higher for those from any ethnic minority group, the lowest quintile of socioeconomic status, and those born preterm or with low birthweight. 345 (44%) of 784 children had a single affected anatomical site. Disorders of the brain and visual pathways affected 378 (48%) of 784 children. Interpretation: BCVIS2 provides a contemporary snapshot of the heterogeneity, multi-morbidity, and vulnerability associated with childhood visual disability in a high-income country. These findings could facilitate developing and delivering health care and planning of interventional research. Our findings highlight the importance of including childhood visual disability as a sentinel event and metric in global child health initiatives. Funding: Fight for Sight, National Institute for Health Research, and Ulverscroft Foundation.